Affective and psychotic reactivity to daily-life stress in adults with 22q11DS: a study using the experience sampling method - Schneider, Maude; Vaessen, Thomas; Duin, Esther D. A. van; Kasanova, Zuzana; Viechtbauer, Wolfgang; Reininghaus, Ulrich; Vingerhoets, Claudia; Booij, Jan; Swillen, Ann; Vorstman, Jacob A. S.; Amelsvoort, Thérèse van; Myin-Germeys, Inez (Journal of neurodevelopmental disorders, 2020)
22q11.2 deletion syndrome (22q11DS) is a genetic disorder associated with an increased risk of psychiatric disorders. Vulnerability for psychopathology has been related to an increased reactivity to stress. Here, we examined affective states, perceived stress, affective and psychotic reactivity to various sources of environmental stress using the experience sampling method (ESM), a structured diary technique allowing repeated assessments in the context of daily life. Adults with 22q11DS (n = 31; age, 34.1 years) and matched healthy controls (HCs; n = 24; age, 39.9 years) were included. ESM was used to assess affective states, perceived stress, and stress reactivity. Data were analyzed using multilevel regression models. Adults with 22q11DS displayed overall higher levels of negative affect but comparable levels of positive affect compared to HCs. Higher levels of perceived stress were reported by individuals with 22q11DS. Comparable affective and psychotic reactivity in relation to all types of environmental stress was observed between the two groups. The results point toward higher levels of negative affect and differences in the perception of daily hassles in 22q11DS but no difference in affective or psychotic reactivity to stress. This study contributes to the growing literature regarding the impact of stress on the development of psychopathology in the 22q11DS population.